In-line monitoring of the photooxidation behaviour of a PP/clay nanocomposite through creep measurements. (August 2016) - La Mantia, F.P.; Biondo, M.; Ceraulo, M.; Mistretta, M.C.
Abstract: The photooxidation behaviour of a polypropylene/organomodified clay nanocomposite sample has been monitored by means of a new apparatus through the record of the creep curves measured while the sample is subjected to the contemporary action of temperature, tensile strength and UV radiation. The creep curves of the irradiated samples are higher than those of the non-irradiated samples and the curves diverge when the molecular weight begins to decrease because of the degradation. At the same the formation of carbonyl groups is observed. The creep curves of the non-irradiated and irradiated samples give, then, an immediate evaluation of the begin and of the development of the photooxidation. This behaviour is more pronounced for the nanocomposite because of the more photooxidation kinetics of this material.